The Role of Artificial Intelligence in Personalizing Learning for Each Student - Susilo, Tarsisius (Journal International of Lingua and Technology, 2024)
Artificial Intelligence (AI) has become one of the major technological innovations in modern education. This article explores the role of AI in personalizing each student's learning. Individual learning is a learning method that adapts each student's learning experience to their needs, abilities and interests. AI enables this personalization of learning to be more efficient and productive. AI plays an important role in personalizing each student's learning. With the ability to analyze data, deliver personalized content, provide better feedback, and predict student progress, AI creates a more adaptive and effective learning environment. However, it should be remembered that the role of the teacher as a learning facilitator is still very important in the use of AI, because human interaction is still an important factor in an effective learning process. The method used in this research is a quantitative method. Researchers conducted a survey using a Google Form which consisted of 15 sentences related to the search title. The study found that applying artificial intelligence (AI) to personalize each student's learning produces significant tracking effects in educational settings. Overall, the use of AI in personalized learning has a significant positive impact on education. However, this requires careful oversight and regulation to ensure that this technology is used properly and provides maximum benefit to all students. The limitation of this research is that the researcher only conducted research in schools, and the researcher did not conduct research directly in schools, but distributed a survey link on a Google form which contained statements about the role of artificial intelligence (AI) in individualization. learning of each student.